Elasticity of Factor Substitution in Cross-Section Production Functions - Fishelson, Gideon (The Review of Economics and Statistics, 1979)
Petroleum Institute, Petroleum Facts and Figures, Washington, D.C., 1971. , Basic Petroleum Data Book, Washington, D.C., 1976. Burright, Burke, and John Enns, Econometric Models of the Demand for Motor Fuel, Rand Report R1561-NSF, Rand Corporation, Santa Monica, Calif., 1975. Chase Econometrics Assoc., Inc., Effect of Tax and Regulatory Alternatives on Car Sales and Gasoline Council on Environmental Quality, 1974. Dahl, Carol A., American Energy Consumption, 'Extravagant or Economical': A Study of Gasoline, Resources and Energy (forthcoming). , Refinery Mix in the U.S., Canada and the E.E.C.. manuscript, Wayne State University, 1979. Houthakker, Hendrik S., Phillip K. Verleger, Jr., and Dennis P. Sheehan, Dynamic Demand Analysis for Gasoline and Residential Electricity, Journal of Agricultural Economics 56 (May 1974), 412-418. Keck, Carol A., Nathan Erlbaum, Patricia L. Milic, and Michael Trentacost, Changes in Individual Travel Behavior during the Energy Crisis, 1973-1974, New York Department of Transportation, Planning and Research Bureau, Preliminary Research Report 67, New York, N.Y., 1974. Motor Vehicle Mfg. Assoc., Auto Facts and Figures, Detroit, MI., various years. Norling, Carol Dahl, Demand for Gasoline, Ph.D. Thesis, University of Minnesota, Minneapolis, MN. Office of Energy Systems Passenger Car Use of Gasoline: Analysis of Policy Options, Federal Energy Administration, Washington, D.C., 1975. Ramsey, James, G. Rash, and B. Allen, An Analysis of the Private and Commercial Demand for Gasoline, this REVIEW 57 (Nov. 1975), 502-507. Sims, Christopher A., Money, Income, and Causality, The Economic Review 62 (Sept. 1972), 540-552. U.S. Department of Commerce, Business Statistics, Washington, D.C., various years. , Statistical Abstract of the United States, Washington, D.C., various years. , Survey of Current Business, National Income Accounts Supplement, Washington, D.C., various years. U.S. Department of Transportation, Highway Statistics Summary to 1965, Washington, D.C., 1965. , Highway Statistics, Washington, D.C., various years. U.S. Government Printing Office, Economic Report of the President, Washington, D.C., 1975. Wildhorn, Sorrel, Burke K. Burright, John H. Enns, and Thomas F. Kirkwood, How to Save Gasoline: Public Policy Alternatives for the Automobile, Rand Report R1560-NSF, Rand Corporation, Santa Monica, Calif. (1974).